Ameliorative effect of ferruginol on isoprenaline hydrochloride‐induced myocardial infarction in rats. Issue 2 (18th September 2020) - Zhang, Xudong; Li, Xiaojiang; Wang, Chunlan; Li, Haijun; Wang, Lijun; Chen, Yu; Feng, Jingbin; Ali Alharbi, Sulaiman; Deng, Yue
Abstract: Cardiovascular‐related diseases continue to be a leading cause of death globally. Among ischemic‐induced cardiac diseases, myocardial infarction (MI) is reported to be of an alarming value. Despite numerous improvements in the medical intrusions, still this armamentarium fails to be effective in managing the illness without setbacks. Ferruginol (FGL) is a major polyphenols and terpenoids with numerous pharmacological activities including antioxidant and anti‐inflammatory. Following, this work was aimed to explore the cardio protective effect of FGL (50 mg/kg) in isoprenaline hydrochloride (ISO)‐induced MI in experimental rats. After treatment with FGL in ISO‐induced MI in rats, noticeable changes were observed in the experimental rats. Injection of ISO to rats resulted in the augmented cardiac weight, serum cardiac markers (creatine kinase, creatine kinase‐MB, cardiac troponin T, and Cardiac troponin I), lipid peroxidation end products (thiobarbituric acid‐reactive substance and lipid hydroperoxides), reduced endogenous antioxidants (superoxide dismutase, catalase, glutathione peroxidase, and glutathione), reduced ATPase activity, and escalated pro‐inflammatory cytokines (interleukin‐6, tumor necrosis factor‐α, and nuclear factor‐κB) levels. Interestingly, the FGL supplementation to the ISO‐treated rats revealed the diminished heart weight, reduced cardiac markers, and lipid peroxidation. FGL also possessed the improved antioxidants status and diminished pro‐inflammatory mediator levels. The outcomes of histological analysis also evidenced the cardio protective role of FGL. Treatment with FGL reduced the cardiac damage biomarkers maintained to near normal levels in ISO‐induced rats. These study findings disclose the prospective capability of FGL in the treatment of MI in the future.